Selective Hierarchical Aluminosilicates for Acetalization Reaction with Propylene Glycol - Hartati Hartati; Mardi Santoso; Hadi Nur; Leaw Wai Loon; Hasliza Bahruji; Imroatul Qoniah; Didik Prasetyoko (Universitas Gadjah Mada, 2019)
Hierarchical micro-mesoporous aluminosilicates nanoparticles were synthesized at different of Si/Al ratios and were directly used as a solid acid catalyst for acetalization reaction with propylene glycol. TEM and N2 adsorption analysis of the resulting aluminosilicates revealed the formation of the hierarchical structure occurs on the Si/Al ratio increases the formation of mesoporous within the structure of aluminosilicate. The aluminosilicates exhibit high selectivity towards acetalization reaction in comparison with the homogeneous PTSA. The presence of mesoporous structures is crucial for increased conversion and selectivity of the reaction which presumably due to the improved diffusion of substrate to reach acid sites.